Smallholder duck farming: a potential source of livelihood in haor women in Bangladesh - Parvez, Shihan; Miah, M Yousuf; Khan, MH (Asian Journal of Medical and Biological Research, 2020)
An experiment was carried out to investigate the effects of feed supplementation on growth performance of Jinding duckling in Haor Household. Nine hundred unsexed day old ducklings were considered for the feeding trial. Duckling were divided into three dietary treatments having 3 replications (50 duckling per replication) and reared on littered floor in an open sided house by providing 0.14 m² floor space per bird. Dietary treatments Group 0 was considered as control or full scavenging group, fed mash feed to the other group 25 g and 50 g per duck per day. Body weight and body weight gain were improved significantly (p<0.05) with the increasing levels of feed supplementation compared to no feed supplementation group during the period of 4-12 weeks. The average net return of per duckling of 25 g dietary group was significantly (p<0.05) higher than that of no supplementation group and 50 g dietary group throughout the experimental period. Net return per batch were 1924 BDT in 25 g feed supplementation group at 12 weeks and yearly net profit was 6735 BDT by rearing of 50 ducklings. Benefit–cost ratio was 1:1.30. The result revealed that duck intervention increased duck production, reduce duckling mortality and improved haor women’s source of income and significantly contributes to rural livelihoods. Asian J. Med. Biol. Res. March 2020, 6(1): 73-80